A hybrid model of factors affecting adoption of mobile banking technology between customers of Iranian banks - Asgarnezhad Nouri, Bagher; Soltani, Milad (Serbian Journal of Management, 2019)
This study aims at providing a hybrid model of mobile banking adoption in the banking industry of Iran. Based on reviewing the models of technology adoption, the main effective factors were divided into four general categories including personal, social, organizational and technological factors. The population of the study consisted of the customers of public banks. With regard to the infinity of the population, based on Morgan table, 384 customers were selected as the sample of the study. A standard questionnaire was used to collect the required data for all the research variables. The research hypotheses were tested using structural equation modeling and based on AMOS software. The results show that some personal, social, organizational and technological factors have a positive significant effect on perceived usefulness and perceived ease of use of mobile banking. Perceived usefulness and perceived ease of use have a positive significant effect on the attitude towards mobile banking. In addition, the positive significant effect of attitude towards the use of mobile banking on the tendency to use mobile banking and vice versa was confirmed.